Tg x/2 tgx=tg x/2+tgx Помогите пожалуйста,буду очень благодарен.

Tg x/2 tgx=tg x/2+tgx Помогите пожалуйста,буду очень благодарен.
Гость
Ответ(ы) на вопрос:
Гость
tg(x/2)*2tg(x/2)/(1-tg²(x/2))=tg(x/2)+2tg(x/2)/(1-tg²(x/2)) tg(x/2)=a 2a²/(1-a²)=a+2a/(1-a²) 2a²/(1-a²)=(a-a³+2a)/(1-a³) 2a²/(1-a²)-(3a-a³)/(1-a²)=0 1-a²≠0⇒a≠1 U a≠-1 2a²-3a+a³=0 a(a²+2a-3)=0 a=0⇒tgx/2=0⇒x/2=πn⇒x=2πn,n∈z a²+2a-3=0 a1+a2=-2 u a1*a2=-3 a=-3⇒tgx/2=-3⇒x/2=-arctg3+πn⇒x=-2arctg3+2πk,k∈z a=1 не удов усл
Не нашли ответ?
Ответить на вопрос
Похожие вопросы